4x=3(9-x)

Simple and best practice solution for 4x=3(9-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x=3(9-x) equation:



4x=3(9-x)
We move all terms to the left:
4x-(3(9-x))=0
We add all the numbers together, and all the variables
4x-(3(-1x+9))=0
We calculate terms in parentheses: -(3(-1x+9)), so:
3(-1x+9)
We multiply parentheses
-3x+27
Back to the equation:
-(-3x+27)
We get rid of parentheses
4x+3x-27=0
We add all the numbers together, and all the variables
7x-27=0
We move all terms containing x to the left, all other terms to the right
7x=27
x=27/7
x=3+6/7

See similar equations:

| H(t)=10t-5t | | 9x-23=x+13 | | d/7+3/10=8 | | X^17=3x^2+8 | | X^2+12x-17=3 | | 6.1+y/8=-6.7 | | -4+7v=1+8v-3 | | 9m-(4m-8)=53) | | 3x+6=12+3x | | -2t-2=7t-14-7t | | x/3=5/35 | | 7/4z=42 | | 24=4u+2u | | 16x-7x=81 | | x+3/8=-3 | | 2p+2=63 | | 0=(m+4)(m-4) | | -1+16n=10n-19 | | 7m-20m-10=3 | | (Y-0)=16(x-2) | | 4=z-11/4 | | 10m-2/5=9.60 | | 54+89+x/3=76 | | Y-0=16(x-2) | | 9x=-x+8 | | -13j-12=-12j | | -6t-5=-7t-11 | | 1/2x-2/3=3/4x+1/2 | | -15w=-16-7w | | -15w=-16–7w | | 37+2x=180 | | -16j=-18j+12 |

Equations solver categories